VARIASI ALIRAN GAS PELINDUNG DAN KECEPATAN PENGELASAN MIG PADA PIPA ALUMINIUM 6063 TERHADAP KEKUATAN TARIK DAN CACAT LAS: VARIATIONS OF SHIELDING GAS FLOW RATE AND TRAVEL SPEED ON THE TENSILE STRENGTH AND WELD DEFECTS OF ALUMINUM 6063 PIPES - yozep imanuel; Sulistyono; Fauzan Baananto (Mechanical Engineering Department Polinema Kediri, 2026)
The Metal Inert Gas (MIG) welding process is influenced by welding speed and shielding gas flow rate, which play an important role in determining weld joint quality. This study aims to analyze the effect of variations in shielding gas flow rate and welding speed on the tensile strength and weld defects of Aluminum Alloy 6063. The shielding gas flow rates used were 12 l/min, 14 l/min, and 16 l/min, while the welding speeds were varied at 4 mm/s, 5 mm/s, and 6 mm/s. Tensile strength testing was conducted in accordance with ASTM E8/E8M standards. The results indicate that the combination of a welding speed of 4 mm/s and a shielding gas flow rate of 16 L/min produced the highest tensile strength of 125.97 MPa. An increase in welding speed reduced heat input, resulting in decreased penetration and weld joint quality. Furthermore, non-optimal shielding gas flow rates promoted weld defects such as porosity and oxidation, which contributed to a reduction in the tensile strength of the welded joints